2013
DOI: 10.1002/jbm.a.34879
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible evaluation of barium titanate foamed ceramic structures for orthopedic applications

Abstract: The potential of barium titanate (BT) to be electrically active makes it a material of interest in regenerative medicine. To enhance the understanding of this material for orthopedic applications, the in vitro biocompatibility of porous BT fabricated using a direct foaming technique was investigated. Characterization of the resultant foams yielded an overall porosity between 50 and 70% with average pore size in excess of 30 µm in diameter. A mouse osteoblast (7F2) cell line was cultured with the BT to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…Moreover, BTO is biocompatible [2,3,5], and can serve as a scaffold material that can be activated by electrical fields in order to stimulate osteoblasts proliferation and differentiation of osteoclasts.…”
Section: Medical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, BTO is biocompatible [2,3,5], and can serve as a scaffold material that can be activated by electrical fields in order to stimulate osteoblasts proliferation and differentiation of osteoclasts.…”
Section: Medical Applicationsmentioning
confidence: 99%
“…Furthermore, studies [2,3,5] have shown that this ceramic is biocompatible and can therefore be used for medical applications such as implants.…”
Section: Introductionmentioning
confidence: 99%
“…This inspires the use of an electro-active implant to improve healing and adaptation of the surrounding tissue, instead of external galvanism. Piezoelectric bioceramic could be an excellent alternative to hard tissue repair for its unique electroactivity [10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Nanosized barium titanate (BT), in turn, has been recently gaining application in biomedicine, as a biological nanocarrier for proteins (Ciofani et al 2010a), an uptake enhancer of low-molecular-weight drugs such as doxorubicin (Ciofani et al 2010b), a biomarker for imaging probes (Hsieh et al 2010), and as bone graft material (Ball et al 2014). Polonini et al (2014) performed ecotoxicological tests on three aquatic microorganisms: C. vulgaris, A. flos-aquae, and E. gracilis.…”
Section: Barium Titanate (Batio 3 )mentioning
confidence: 99%